Chemical composition and functional properties of Vicia faba L. from Bangladesh (Bangladesh Journal of Botany, 2010)
Seed-cotyledons of Vicia faba L. an unconventional legume from Bangladesh were analyzed for chemical composition and protein functionality to assess its potential usage as an alternative source of protein. Proximate component in per cent were crude protein 30.57, crude fat 3.22, crude fibre 2.73, ash 3.61 and carbohydrate 59.87. With the exception of methionine plus cystine, the essential amino acids in the seedcotyledons were present at concentrations equal to or greater than those commonly recommended. Least gelation concentration, water and fat absorption capacities were 8.00, 83.86 and 79.43%, respectively. Foaming capacity and foaming stability were 57.19 and 29.78%, respectively. With respect to its nutritive composition and functionality, the pulse appeared to be a potential source of nutrient. Key words: Vicia faba; Chemical composition; Functional properties; Legumes; Bangladesh DOI: 10.3329/bjb.v38i1.5129 Bangladesh J. Bot. 38(1): 93-97, 2009 (June)